Barriers to safe anaesthesia care in South Asian countries: a virtual focus group discussion - Gauhar Afshan; Khan, Robyna Irshad; Karmaliani, Rozina; Ahmed, Aliya; Khan, Fauzia Anis (Journal of the Pakistan Medical Association, 2024)
Objectives: To identify barriers to safe anaesthesia practice across the South Asian region. Method: The qualitative study was conducted from September 2020 to August 2021 at the Department of Anaesthesiology at a leading medical university after getting exemption from the ethics review committee of the Pakistan Society of Anaesthesiologists. The sample comprised anaesthetists from 6 countries of the South Asian Association for Regional Cooperation. Data was collected through a focus group discussion held virtually using the Zoom app on September 22, 2020. The proceedings were transcribed and the data was subjected to thematic analysis. Results: Of the 12 anaesthetists, 4(33.3%) were from India, 3(25%) from Pakistan, 2(16.7%) from Bangladesh, and 1(8.3%) each from Sri Lanka, Nepal and Afghanistan. There were 2 main themes identified; Safe anaesthesia and barriers to safe anaesthesia. They had 4 and 6 subthemes, respectively. The participants agreed that fresh medical graduates were not choosing anaesthesia as a preferred career specialty. One major concern raised was that qualified anaesthetists were leaving their countries for better-paid jobs abroad. Conclusion: The lack of a definition describing qualified anaesthetists in South Asian countries was pointed out. Lack of basic monitoring and drugs, brain drain, lack of ownership, lack of training programmes, lack of accountability, weak leadership, and disconnect between professional societies and governments were identified as the main barriers to safe anaesthesia. Key Words: Safe practice, Anaesthesia, Developing countries, Developed countries.